2012
DOI: 10.1007/s10456-012-9252-6
|View full text |Cite
|
Sign up to set email alerts
|

c-ABL modulates MAP kinases activation downstream of VEGFR-2 signaling by direct phosphorylation of the adaptor proteins GRB2 and NCK1

Abstract: Vascular Endothelial Growth Factor-A (VEGF-A) is a key molecule in normal and tumor angiogenesis. This study addresses the role of c-ABL as a novel downstream target of VEGF-A in primary Human Umbilical Vein Endothelial Cells (HUVEC). On the basis of immunoprecipitation experiments, in vitro kinase assay and RNA interference, we demonstrate that VEGF-A induces the c-ABL kinase activity through the VEGF Receptor-2/Phosphatidylinositol-3-Kinase pathway. By treating HUVEC with the specific tyrosine kinase inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 51 publications
(64 reference statements)
1
18
0
Order By: Relevance
“…To assess a potential role for the Abl kinases in the regulation of endothelial barrier function, we initially evaluated Abl kinase activity following treatment of human microvascular endothelial cells (HMVECs) with the permeability-inducing factors VEGF, thrombin, and histamine. In agreement with previous findings in human umbilical vein endothelial cells (HUVECs) [28,30,31], stimulation of HMVECs with VEGF resulted in Abl kinase activation, as assessed by the phosphorylation of CrkL at tyrosine (Y) 207, an Abl-specific phosphorylation site [32] (Figure 1A ), which was prevented by pre-treatment with the ATP-competitive Abl kinase inhibitor imatinib. Interestingly, pre-treatment with the Src kinase inhibitor su6656 partially blocked Abl kinase activation in response to VEGF stimulation (Figure 1B ), suggesting that the Abl kinases may act downstream of Src family kinases in VEGF-mediated signaling.…”
Section: Resultssupporting
confidence: 91%
“…To assess a potential role for the Abl kinases in the regulation of endothelial barrier function, we initially evaluated Abl kinase activity following treatment of human microvascular endothelial cells (HMVECs) with the permeability-inducing factors VEGF, thrombin, and histamine. In agreement with previous findings in human umbilical vein endothelial cells (HUVECs) [28,30,31], stimulation of HMVECs with VEGF resulted in Abl kinase activation, as assessed by the phosphorylation of CrkL at tyrosine (Y) 207, an Abl-specific phosphorylation site [32] (Figure 1A ), which was prevented by pre-treatment with the ATP-competitive Abl kinase inhibitor imatinib. Interestingly, pre-treatment with the Src kinase inhibitor su6656 partially blocked Abl kinase activation in response to VEGF stimulation (Figure 1B ), suggesting that the Abl kinases may act downstream of Src family kinases in VEGF-mediated signaling.…”
Section: Resultssupporting
confidence: 91%
“…It binds phosphorylated insulin receptor substrate 1 and subsequently activates the MAPK pathway via Ras in response to insulin [30]. This gene is also involved in vascular endothelial growth factor signalling leading to angiogenesis, which is characteristic of proliferative diabetic retinopathy [31]. GRB2 encodes two transcripts in humans [32].…”
Section: Discussionmentioning
confidence: 99%
“…VEGF‐dependent angiogenesis requires p38MAPK activation and this response is dependent on the VEGFR2 co‐receptor neuropilin‐1, along with the VEGFR2 co‐receptor neuropilin‐1, for VEGF‐dependent angiogenesis . Furthermore, it has been reported that the VEGFR2‐dependent phosphorylation of Nck requires the c‐Abl tyrosine kinase .…”
Section: Vegfr2‐dependent Signalling Pathwaysmentioning
confidence: 99%